Penyuluhan dan Pelatihan Perbaikan Kepala Accu untuk Optimalisasi Sistem Kelistrikan Kendaraan - Syaiful Rizal; Kartika Sekarsari; Faraida Nafiri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The Markaz Hadith Bilal bin Rabbah Islamic Boarding School faces obstacles in the maintenance of operational vehicles, especially when there is damage to the components of the Accu head. The absence of human resources who have technical competence in the field of automotive electricity leads to dependence on external workshop services, which has an impact on increasing the operational costs of Islamic boarding schools. This problem also interferes with the smooth running of logistics activities and daily pesantren services. To answer these problems, lecturers and students of the Electrical Engineering and Mechanical Engineering Study Program, Pamulang University, conducted community service activities. This activity aims to increase the technical capacity of students and pesantren managers in independently diagnosing, treating, and repairing Accu heads using simple tools and materials. The activity was carried out with a participatory approach through interactive lecture methods, technical demonstrations, and hands-on practice in the field. The training materials are arranged appropriately so that they are easy for participants with non-technical backgrounds to understand. The evaluation was conducted using descriptive analysis techniques based on the pre-test and post-test results and qualitative observation of the participants' involvement during the training. Twenty participants attended this training. The analysis showed that as many as 65% of participants experienced a significant improvement in conceptual understanding and practical skills after participating in the training. These findings show the effectiveness of the activity in equipping participants with basic vehicle electrical skills. In general, this activity contributes to increasing the technical independence of Islamic boarding schools and opens up opportunities for developing skills-based entrepreneurship in the Islamic boarding school environment.